The happy child program’s intersectionality : prenatal home visit frequency, food insecurity risk symptoms of depression, and parental practices in brazilian women assisted during pregnancy - Biete, Camila (2024)
Food insecurity (FI) is a critical issue in developing countries, particularly in low-resource settings, where it can worsen women’s mental health. Psychosocial factors such as low household income, limited education, multiparity, and vulnerability are linked to depressive symptoms during pregnancy. Additionally, the family environment influences parental practices, which may impact mental health. This study evaluates the association of socioeconomic factors, parental practices, FI risk, and home visit frequency with depressive symptoms in pregnant women enrolled in the Happy Child Program (Programa Criança Feliz—PCF) in the Federal District, Brazil. In this crosssectional study, 132 pregnant women monitored by PCF from May to July 2023 were assessed using a self-administered questionnaire for socioeconomic data, the two-item Triage for Food Insecurity (TRIA) instrument for FI risk, the Scale of Parental Beliefs and Early Childhood Care Practices, and the Beck Depression Inventory-II for depressive symptoms. Most participants were multiparous (87.9%), had low income (under 200 USD/month; 80.8%), presented depressive symptoms (67.4%) and were at risk of FI (81.8%). About half demonstrated adequate parental practices (50.8%) and received four home visits per month during pregnancy (54.5%). Women who received four PCF home visits had a lower prevalence of depressive symptoms compared to those with fewer visits (PR 0.76, 95% CI 0.59–0.98). No significant association was found between FI or parental practices and depressive symptoms. These findings suggest that the PCF home-visiting program may strengthen vulnerable families, support social networks, and improve mental health during pregnancy. Additionally, the results of this study highlight the need for targeted interventions aimed at reducing food insecurity and promoting mental health during pregnancy, particularly among socially vulnerable populations. Furthermore, they reinforce the importance of expanding access to home-visiting programs as an effective strategy to improve maternal mental health and well-being, while fostering healthier prenatal environments for both mothers and their children.